On the far field optical properties of Ag-Au nanosphere pairs - Encina, Ezequiel Roberto (2010)
In this work we study the far field optical properties of heterodimers composed of a silver and a gold nanosphere of the same size, by means of exact electrodynamics calculations based on the generalized multiparticle Mie theory. We analyze the effect of the incident polarization, nanosphere separation, radius and dielectric media on the optical response. The on resonance angular distribution of the scattered radiation is also analyzed. The nonsymmetrical features of this system allow us to evaluate and perform a careful examination of the contributions of absorption and scattering from each individual nanosphere to the total extinction of the system. At variance with the homodimer system, the heterodimer exhibits a simultaneous shift of two plasmonic resonances. This feature constitutes a very useful and accurate way to calibrate both interparticle distance and size at the same time for a given dielectric environment. In this way, we provide a general and complete description of the far field optical properties of this particular nanostructure, which may be valuable for the design and development of plasmonic devices and optical tools and could serve as benchmark calculations for future comparisons with experiments.